2020
DOI: 10.21203/rs.2.17869/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adoption Rates of Electronic Health Records in Turkish Hospitals and the Relation with Hospital Sizes

Abstract: Background : Nation-wide adoption of electronic health records (EHRs) in hospitals has become a Turkish policy priority in recognition of their benefits in maintaining the overall quality of clinical care. The electronic medical record maturity model (EMRAM) is a widely used survey tool developed by the Healthcare Information and Management Systems Society (HIMSS) to measure the rate of adoption of EHR functions in a hospital or a secondary care setting. Turkey completed many standardizations and infrastructur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been found that at least 60% of hospitals between the United States, Europe, and Asia still have a basic EMR system, 62 where a majority are classified as stages 0 to 2 according to the Healthcare Information and Management Systems Society’s Electronic Medical Record Adoption Model. The fact that our system stemmed from a basic HIS itself (stage 1) renders its results promising for hospitals with basic HIS and limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that at least 60% of hospitals between the United States, Europe, and Asia still have a basic EMR system, 62 where a majority are classified as stages 0 to 2 according to the Healthcare Information and Management Systems Society’s Electronic Medical Record Adoption Model. The fact that our system stemmed from a basic HIS itself (stage 1) renders its results promising for hospitals with basic HIS and limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we measured patient rating of the overall quality of care by using a single question using a 5-point Likert scale (1 = excellent, 2 = very good, 3 = good, 4 = fair, 5 = poor). Finally, we included patient demographics such as age group, gender, and race, and hospital characteristics such as hospital location (based on United States Census Bureau's urban and rural definitions of urban or rural) (25), size (small: 0–99 beds, medium: 100–399 beds, large: 400+ beds) (26,27), and teaching status (yes/no). A teaching hospital, also known as an academic medical center, partners with medical and/or nursing schools, education programs, and research centers to improve health care delivery through learning and research (28).…”
Section: Methodsmentioning
confidence: 99%
“…We first obtain as the maximizer of the penalized partial likelihood where is the log partial likelihood associated with and is the elastic net penalty function, which is frequently used to overcome high dimensionality and collinearity of features with α = 1 corresponding to the standard LASSO and α = 0 corresponding to the ridge penalty [28]. The non-negative penalty parameter can be selected via standard tuning criteria including the AIC, BIC or cross-validation.…”
Section: Step I: Training L Local Risk Prediction Modelsmentioning
confidence: 99%